Mathematics Literacy of Grade 4 Elementary School Students in Solving HOTS Type Mathematics Problems - Aulia, Hantika; Habibi, Habibi; Risnawati, Risnawati (Journal of Educational Sciences, 2023)
The purpose of this study was to determine the level of mathematical literacy possessed by students related to the completion of HOTS-type questions found in FPB and KPK content. Written exams, interviews, and documentation are the three data collection methods used in this study. The participants in this study were three children at Grade 4 Elementary School 001 Air Tiris. The level of the students' mathematical abilities ranged from high, medium, and low. The ability to solve problems and frame problems, the ability to apply mathematics, and the ability to communicate are the three components of mathematical literacy skills used in this study. The results of the study show that the use of HOTS-type math problems for learning mathematics improves problem solving, application of mathematics, and communication. According to the introduction to the section, There are still wrong answers, so each student's mathematical literacy is unique. Students have demonstrated the ability to understand and construct problems, particularly in the areas of problem solving and problem formulation. Students' conceptual and procedural problem-solving abilities in mathematics are limited, and this limits their ability to adequately apply mathematics to real-world situations. In terms of communicating, not all students are able to write responses in a logical way. In addition, they do not write down clear problem-solving strategies and do not include conclusions.